Termination of employment contracts by mutual consent and labor market fluidity - Cyprien Batut; Eric Maurin (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2020)
In many countries, the termination of employment contracts has to be either on employer initiative or on employee initiative. In 2008, the French government introduced a change in doctrine: it became possible to terminate employment contracts by mutual consent at a lower cost. We show that the reform was followed by a very significant increase of about 20% in outflow of permanent workers as well as by the replacement of around 10% of dismissals for cause by terminations by mutual consent. By promoting terminations by mutual consent, the reform has improved labor market fluidity and reduced the risks of labor disputes.
Keywords: J23; J52; J63; 330; employment termination; dismissal; quit; labor litigation; severance payment